Mastite infecciosa equina: uma visão geral da doença - Motta, Rodrigo Garcia [UNESP]; Nardi Júnior, Geraldo de [UNESP]; Perrotti, Isabella Belletti Mutt [UNESP]; Ribeiro, Marcio Garcia [UNESP] (My University, 2011)
Mastits is considered uncommon disease in mares. Streptococcus equi, Staphylococcus sp., Corynebacterium sp., Actinobacillus sp., Nocardia sp. and enterobacterias are major microorganisms involved in equine mammary infections. The disease is commonly related to traumatic lesions in mammary glands and teats. Edema, fibrosis, masses to palpation of glands, and viscous to seropurulent milk are mainly clinical signs observed in affected animals. The diagnosis is based on clinical exam of mammary glands and microbiological culture of the milk. There are no standard to use of indirect exams on diagnosis, including California Mastits Test and Somatic Cell Count. Systemic antimicrobials are recommended in therapy, based on previous “in vitro” susceptibility microbiological test. No specific control measures are indicated in equine mastits. The present study reviewed the mastits in mares, with emphasis to etiology, epidemiology findings, clinical manifestation, diagnosis, treatment and control aspects.

A Mastite em éguas é considerada uma doença rara sendo o Streptococcus equi, Staphylococcus sp., Corynebacterium sp., Actinobacillus sp., Nocardia sp. e as enterobacterias os micro-organismos mais frequentemente envolvidos. A doença está relacionada a injúrias e traumas nas mamas e tetos. Edema e fibrose da glândula mamária, leite com aspecto viscoso ou muco-purulento são observados nos casos de mastite clínica. O diagnóstico é baseado no exame clínico da mama associado ao cultivo microbiológico do leite. Os métodos indiretos para o diagnóstico de mastite subclínica como California Mastits Test e Contagem de Células Somáticas não são padronizados para a espécie em questão. A terapia para a mastite equina é baseada no uso sistêmico de antimicrobianos, com base nos resultados obtidos no teste “in vitro” de sensibilidade microbiana. Não há medidas de controle específicas para a mastite equina. Objetivou-se neste estudo revisar os principais aspectos relacionados a mastite em éguas com ênfase na etiologia, epidemiologia, sinais clínicos, diagnóstico, tratamento, medidas de controle e profilaxia.
Infectious mastitis in mare: an overview of disease
Keywords: Mastits; Mares; Microbiological cultura; Reviewed; Mastite; Éguas; Cultura microbiológica; Revisão